Macronutrient Distribution on the North Coast of Pekalongan City, Central Jawa, Indonesia: Implications for Water Quality - Andreas Roy; Megasari Intan; Trenggono Mukti; Hendrayana Hendrayana; S Oktaviani Ade (E3S Web of Conferences)
The current condition of Pekalongan North Coast waters is faced with environmental problems that directly impact nutrient distribution, such as waste disposal from industry, ports, settlements, tidal problems, and mangrove damage. This study aims to determine the distribution of nutrients and the status and implications of water quality using the CCME-Water Quality Index method. The research was conducted in January 2023 in 3 areas, namely Mrican River, Pencongan River, and Wonokerto Beach with 17 sampling stations (6 in each river and five on the beach). Data analysis of this study used Principal Component Analysis (PCA) and CCME-Water Quality Index methods. The results of the highest macronutrient distribution in the Mrican River at RW 4 station were nitrate 1.4162 mg/L, phosphate 1.1891 mg/L, and silicate 2.5485 mg/L. The CCME-Water Quality Index method results show that the waters are classified as low status. This condition can cause pollution implications that can damage aquatic ecosystems and interfere with aquatic biota's life processes.